Analysis of Carburizing Effect Due to Hardness and Microstructure on ST 60 Steel Using Carbon Particle with 80 Mesh - Pramuko Ilmu Purboputro; Radix Ekaputra (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to determine the effect of pack carburizing with annealing treatment using coal carbon, coconut shell carbon, mangrove tree carbon on the microstructure and hardness of the ST60 steel material. The pack carburizing process is carried out at a temperature of 900Â°C and held for 60 minutes by cooling to room temperature so that the carbon atoms are removed. In microstructure testing (SEM) on raw material, pearlite and ferrite phases are formed, after pack carburizing the phase is formed pearlite, ferrite and coated with graphite from carbon atoms causing the hardness of the specimen to increase in the pearlite phase exposed to carbon. The results of the Rockwell Hardness test on raw material 52.3 HRA after the pack carburizing process, the hardness of the material has increased which is found in coal carbon of 62.2 HRA, coconut shell carbon of 64.8 HRA and mangrove carbon of 60.7 HRA from the test. the chemical composition of the results obtained in the raw material condition of 0.404 when in pack carburizing increased each material coal carbon by 0.829, coconut shell carbon by 0.88, mangrove carbon by 0.76. So the carbon intake during pack carburizing is directly proportional to the hardness produced in the material.